Comparative Analysis of Factors Affecting Firm Value in the Conventional and Sharia Stock Index - Dewi, Amanda Puspita; Sembiring, Ferikawita Magdalena (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2024)
This research aims to determine the effect of liquidity, profitability, good corporate governance and investment opportunity set on firm value in conventional and sharia stock index, namely is in Investor33 Indeks an Jakarta Islamic Index listed on the Indonesia Stock Exchange (IDX) for the 2017-2022 period. The sample selection used a purposive sampling technique, 21 samples of companies from 48 populations of Indeks Investor33 and 11 samples of companies from 53 populations of Jakarta Islamic Index. The data collection technique used was secondary data with data analysis technique using panel data regression analysis and using Eviews 10 software. The best model was obtained, namely is Fixed Effect Model (FEM). Based on the results of this research, it shows that partial liquidity has no effect on firm value in Investor33 Indeks and Jakarta Islamic Index. Profitability partially has a positive effect on the firm value in Investor33 Indeks, while profitability has no effect on the firm value of Jakarta Islamic Index. Good corporate governance partially has no effect on the firm value of Indeks Investor33, while good corporate governance has a positive effect on the firm value of Jakarta Islamic Index. Investment opportunity set partially has a positive effect on the firm value of in Investor33 Indeks and Jakarta Islamic Index. Apart from that, simultaneously liquidity, profitability, good corporate governance and investment opportunity set influence the firm value of in Investor33 Indeks and Jakarta Islamic Index. In this research, the firm value on the conventional and sharia stock indexes with the best performance on the IDX cannot be separated from other factors that can influence investors in assessing a company.